مدى تضمن أبعاد مفهوم العيش المشترك في منهج الدراسات الاجتماعية العماني - العجمية, حوراء; المعمري, سيف (جامعة الوادي - University of Eloued, 2023)
هدفت الدراسة الحالية إلى الكشف عن مدى تضمن أبعاد مفهوم العيش المشترك في مناهج الدراسات الاجتماعية العماني من وجهة نظر معلميها، تكونت العينة من (13) معلم ومعلمة في محافظة مسقط، تم اختيارهم بطريقة قصدية من مجموع (30) معلماً ومعلمةً خضعوا لبرنامج تدريبي حول العيش المشترك، وقد تم الحصول على بيانات الدراسة بواسطة مقابلة شبه مقننة. وأظهرت نتائج التحليل النوعي عن فئتين رئيستين أولهما درجة اهتمام المناهج العمانية بالعيش المشترك وثانيهما مظاهر اهتمام المناهج العمانية بالعيش المشترك وقد نوقشت هذه النتائج، ثم خرجت الدراسة بعدد من التوصيات حول صور ظهور مفهوم العيش المشترك في منهج الدراسات الاجتماعية ، وأهميته في ضوء النتائج التي توصلت إليها. Abstract: The curren study aimed to reveal the extent to which the dimensions of the concept of coexistence in the Omani social studies curriculum are guaranteed from the point of view of its teachers, the sample consisted of (13) teachers in Muscat province, selected in a deliberate manner from a total of (30) teachers who underwent a training program on co-existence, and the study data was obtained by a semi-codified interview. The results of the qualitative analysis on two main categories, the first of which showed the degree of interest of the Omani curriculum in coexistence and the second of the interest of the Omani curriculum in coexistence and these results were discussed, and then came out with a number of recommendations on the images of the emergence of the concept of co-existence in the curriculum of social studies, and its importance in the light of its findings.
من وجهة نظر معلميها
مقال
Keywords: تصورات المعلمين؛ معلمي الدراسات الاجتماعية؛ عيش مشترك؛ تعايش سلمي؛ مناهج الدراسات الاجتماعية); (perceptions of teachers, teachers of social studies, co-existence, peaceful coexistence, social studies curricula).